Investigation of the Consolidation Drainage of High Water Content Clay by Siphon Method through Unsaturated Filter. (2015) - Soda, Shodai; Ishikura, Ryohei; Yasufuku, Noriyuki; Handoko, Luky
Abstract: Recently, the disposal of dredged soil has become a worldwide problem. In order to utilize high water content soil material, it is essential to dewater and increase the soil strength. There are urgent demands for developing an alternative new method to dewater the dredged soils in more economical and environment friendly standpoint. Furthermore, by using adsorption effect of porous material such as granular blast furnace slag, there is possibility to establish purification technology of contaminated soil. In this paper, the siphon method is proposed to dewater the high water content dredged soil with horizontally installed plastic board drain and filter material. In order to investigate the availability and effectiveness of this method, series of tests were conducted to investigate the dewatering behaviour and strength of dredged soil with vacuum and siphon methods by using different materials as filter, such as Toyoura sand, zeolite, granular blast furnace slag. High water content dredged soil can be consolidated by using siphon method with saturated filter material such as Toyoura sand. However, it was impossible to dewater dredged soil by using siphon method with unsaturated porous filter material. The water retention tests of soil by using centrifuge method was performed to clarify the mechanism of preventing consolidation dredged soil. The test cannot find an accurate soil-water retention curve of dredged soil because of volume change. The water retention test by suction method was performed and clarify the mechanism that prevents consolidation dredged soil. The cause that prevents consolidation of dredged soil has been presumes by clarifying the air entry value. In addition, degree of saturation and suction in dredged soil and filter material has been clarified by using aquameters. The examination whether consolidation of dredged soil on various conditions focused on height of dredged soil and filter material is performed based on the revealed mechanism.